(untitled) (Research, Society and Development, 2026)
Otohematoma is a condition characterized by the accumulation of blood between the auricular cartilage and the skin of the auricle, being relatively common in dogs and less frequent in cats. In cats, it is usually associated with otitis externa, allergic dermatopathies, ectoparasites, and trauma resulting from intense pruritus and head shaking. The diagnosis is clinical, based on inspection and palpation of the ear, observing an increase in floating volume on the concave side of the auricle. Treatment can be conservative or surgical, the latter being the most appropriate to reduce recurrence and permanent deformities. The present study aims to report a case of otohematoma in a domestic cat, addressing the clinical findings, diagnosis, treatment instituted, and patient evolution, in addition to reviewing the literature on the etiopathogenesis, diagnostic methods, and therapeutic approaches to the condition. The case reinforces the importance of identifying and treating the primary cause to prevent recurrence and ensure a better aesthetic and functional prognosis.